2016
DOI: 10.1016/j.ssmph.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The association between anti-immigrant policies and perceived discrimination among Latinos in the US: A multilevel analysis

Abstract: Research has found a strong inverse association between discrimination and health and well-being. Most of these studies have been conducted among African-Americans, and have examined the relationship at the individual-level. To fill these gaps in knowledge we estimated the prevalence of perceived discrimination among a nationally representative sample of Latino adults in the US, and investigated the association between state-level anti-immigrant policies and perceived discrimination. We merged survey data with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(103 citation statements)
references
References 38 publications
5
95
0
Order By: Relevance
“…Though tough anti‐immigration measures are often proposed to enforce existing laws, evidence suggests that the support behind such policies is driven by a desire to protect against symbolic threats to an Anglocentric national American identity rather than to enforce rule of law (Mukherjee, Molina, & Adams, ). Given that policies can be used to defend against threats to an American national identity, we propose that the salience of anti‐immigrant rhetoric influences the interpretation of identity‐related social encounters because they may communicate to ethnic minorities that they are not seen as full Americans (Almeida, Biello, Pedraza, Wintner, & Viruell‐Fuentes, ). Indeed, a Pew Research report finds that half of Latin Americans surveyed reported serious concerns about their place in the United States and believe their situation has worsened since 2017 (Pew Research Center, ).…”
Section: Identity Questioningmentioning
confidence: 99%
“…Though tough anti‐immigration measures are often proposed to enforce existing laws, evidence suggests that the support behind such policies is driven by a desire to protect against symbolic threats to an Anglocentric national American identity rather than to enforce rule of law (Mukherjee, Molina, & Adams, ). Given that policies can be used to defend against threats to an American national identity, we propose that the salience of anti‐immigrant rhetoric influences the interpretation of identity‐related social encounters because they may communicate to ethnic minorities that they are not seen as full Americans (Almeida, Biello, Pedraza, Wintner, & Viruell‐Fuentes, ). Indeed, a Pew Research report finds that half of Latin Americans surveyed reported serious concerns about their place in the United States and believe their situation has worsened since 2017 (Pew Research Center, ).…”
Section: Identity Questioningmentioning
confidence: 99%
“…More than any single policy or program, it is a state's combination of policies that shape the context of settlement and incorporation, and reinforce attitudes towards immigrants. Within the different policy contexts across US states, immigrants may be included through extended social and economic rights, such as the ability to pursue higher education, or excluded by lack of protections, such as in the workplace, or excluded through discrimination and active surveillance and enforcement by local law enforcement (Almeida, Katie, Pedraza, Wintner, & Viruell-Fuentes, 2016;Flores, 2010;Kline, 2017). As a result, the determinants of immigrant health vary across states.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular importance, the apparent divergence between neighbourhood 'welcome' and 'discrimination' in explaining cyberbullying risk among immigrants and non-immigrants could indicate that cohesion within a neighbourhood may be associated with risk through separate pathways for immigrants compared to non-immigrants. For example, an individual's perception of an 'unwelcoming' neighbourhood may be a more adequate proxy than 'discrimination' in explaining the link between inclusion/exclusion and risk of cyber-victimization for immigrants, and could reflect how rising anti-immigration sentiment in North America (31,49) is operating in subtler ways in the Canadian context than more overt neighbourhood-level discriminatory acts. Conversely, it is also plausible that the absence of an association between neighbourhood discrimination and cyber-victimization for immigrants reflects underlying differences in socialization processes related to time since arrival among immigrants (50).…”
Section: Cyber-victimization Immigrant Status and Sexmentioning
confidence: 99%
“…With the growing ubiquity of internet use, the unique challenges of the resettlement process, and rising anti-immigrant policies (31,32), it is also very plausible that the landscape of cyberbullying among immigrants may be influenced by the neighbourhood microcosm, including local antiimmigrant sentiment, discrimination, and violence. In one of the only known studies to date examining neighbourhood-level influences on cyberbullying perpetration, Khoury Kassabri et al…”
Section: Introductionmentioning
confidence: 99%